287 Retrospective Review of a Single Surgeon 5-Year Experience of Paediatric Breast Reconstruction - Challenges, Experience, and the Increasing Role of Lipofilling. (19th August 2022) - Nelson, A; Taghizadeh, R; Hassan, D
Abstract: Aim: This case series reviews the presentation, clinical and surgical management of paediatric breast cases undertaken by a single surgeon. The series demonstrates the powerful role of lipomodelling when used with breast reshaping techniques to achieve good outcomes and avoid the need to commit young patients to breast implants. Method: Retrospective analysis of paediatric breast referrals to a single surgeon at a regional plastic surgery breast reconstruction unit over a 5-year period. Results: In a 5-year period, 15 cases which presented in childhood to a tertiary paediatric centre were referred on to our regional plastic surgery breast reconstruction unit. Two patients underwent correction of breast hypoplasia secondary to Poland's syndrome. Nine patients presented for breast asymmetry with associated tuberous deformity. One patient had maldevelopment of a breast secondary to a burn's contracture. Two patients presented with gigantomastia and one patient with juvenile fibroadenomas. Conclusions: Paediatric breast abnormalities represent a small but important caseload for a breast reconstructive surgeon. This case series demonstrates the need for careful assessment and an individualised surgical plan for each patient. The surgical plan must achieve a satisfactory outcome whilst minimising the need for further procedures as the patient grows. It is the senior surgeon's preference to avoid breast implant-based reconstruction where possible. In all but one case lipomodelling combined with reshaping of the native tissue was used to good effect.